2013
DOI: 10.1007/s12020-013-0055-3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of sensorial innervation in the newborn female rats affects the activity of hypothalamic monoaminergic system and steroid hormone secretion during puberty

Abstract: There is evidence that sensory innervation plays a role regulating ovarian functions, including fertility.Since sensory denervation by means of capsaicin in newborn female rats results in a lower response togonadotropins, the present study analyzed the effects that sensory denervation by means of capsaicin in neonatal rats has on the concentration of monoamines in the anterior(AH) and medium (MH) hypothalamus, and on steroid hormone levels in serum. Groups of newborn female rats were injected subcutaneously wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The subcutaneous injection of capsaicin to newborn female rats resulted in lower monoaminergic activity in the hypothalamus when rats reached 20 days of life [ 27 ]. Moreover, we have previously shown that in rats, treatment with capsaicin on the third day of life resulted in a decrease in serum estradiol and progesterone concentrations and that this result was not observed when the treatment with capsaicin was performed in new-born rats [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The subcutaneous injection of capsaicin to newborn female rats resulted in lower monoaminergic activity in the hypothalamus when rats reached 20 days of life [ 27 ]. Moreover, we have previously shown that in rats, treatment with capsaicin on the third day of life resulted in a decrease in serum estradiol and progesterone concentrations and that this result was not observed when the treatment with capsaicin was performed in new-born rats [ 28 ].…”
Section: Introductionmentioning
confidence: 99%